New cyclen-cored dendrimers functionalized with pyrene: Synthesis characterization, optical and photophysical properties. Issue 13 (29th March 2017) - Cevallos-Vallejo, Amanda; Vonlanthen, Mireille; Porcu, Pasquale; Ruiu, Andrea; Rivera, Ernesto
Graphical abstract: Highlights: New cyclen cored dendrimers with pyrene up to second generation were synthesized. Fluorescence spectra of the dendrimers exhibited monomer and excimer emission. More intense excimer emission was observed in the highest generation dendrimer. Abstract: New cyclen (1, 4, 7, 10-teraazacyclododecane) cored dendrimers up to the second generation, functionalized with 4, 8 and 16 pyrene units, respectively, were synthesized following a convergent procedure. All new compounds were characterized by NMR spectroscopies and ESI or MALDI TOF mass spectrometry. The optical and photophysical properties of the new dendrimers were studied in THF solution. Absorption spectra showed the typical absorption bands of pyrene moieties. In the fluorescence spectra, monomer as well as excimer emission were observed for all compounds. An increased proportion of excimer emission was observed in the dendrimer of the highest generation.